2014
DOI: 10.1002/ijc.28913
|View full text |Cite
|
Sign up to set email alerts
|

SDHB mutations are associated with response to temozolomide in patients with metastatic pheochromocytoma or paraganglioma

Abstract: Cyclophosphamide-dacarbazine-vincristine regimen is recommended for the treatment of malignant pheochromocytoma and paraganglioma (MPP); however, dacarbazine is the only recognized active drug in neuroendocrine tumours. We investigated the therapeutic benefit of temozolomide (TMZ), an oral alternative to dacarbazine, in patients with MPP. This is a retrospective study of consecutive patients with documented progressive MPP. We examined the correlation between Succinate dehydrogenase B (SDHB) mutation and O(6)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 35 publications
3
135
0
2
Order By: Relevance
“…Knowledge of the SDHx-mutated status is critical for the follow-up and clinical management of patients and of their relatives. On the basis of an early knowledge of the SDHx mutational status, surgeons may decide to (36). Although these results will need to be evaluated in larger, prospective, and comparative studies, they nevertheless pave the way toward personalized medicine for inherited PPGL.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the SDHx-mutated status is critical for the follow-up and clinical management of patients and of their relatives. On the basis of an early knowledge of the SDHx mutational status, surgeons may decide to (36). Although these results will need to be evaluated in larger, prospective, and comparative studies, they nevertheless pave the way toward personalized medicine for inherited PPGL.…”
Section: Discussionmentioning
confidence: 99%
“…Temozolomide is expected to have less toxicity than the CVD regimen. Recently, a team from the Gustave Roussy Institute has reported that the response rates of MPP patients on temozolomide therapy are similar to those of MPP patients on the CVD regimen (48).…”
Section: European Journal Of Endocrinologymentioning
confidence: 98%
“…MGMT plays a role in the cell detoxification process by relieving O 6 -methylguanine adducts. The recently published findings of researchers from the Gustave Roussy Institute and Hospital Georges Pompidou indicate that tumors associated with SDHB mutations are MGMT deficient and thus might respond better to CVD or temozolomide therapy than apparently sporadic tumors that are not associated with somatic mutations in the SDHB gene (48). Nevertheless, some carriers of SDHB mutations do not respond to CVD therapy (19).…”
Section: Predictors Of Responsementioning
confidence: 99%
“…Detection of a PPGL-related somatic mutation in the tumour of a germ line 'negative PPGL' suggests sporadic disease, and, consequently, averts the need for screening the patient's relatives. Moreover, identification of a somatic mutation provides insights into tumour biology, and might guide targeted therapies, especially in patients with metastatic disease (when treatment options are limited) [56][57][58][59] . The Study Group recommends that the analysis of somatic mutations in PPGLs be carried out whenever possible.…”
Section: Somatic Variantsmentioning
confidence: 99%